Genetic mechanisms of target antigen loss in CAR19 therapy of acute lymphoblastic leukemia. (October 2018) - Orlando, Elena; Han, Xia; Tribouley, Catherine; Wood, Patricia; Leary, Rebecca; Riester, Markus; Levine, John; Qayed, Muna; Grupp, Stephan; Boyer, Michael; Moerloose, Barbara; Nemecek, Eneida; et al.
Abstract We identified genetic mutations inCD19 and loss of heterozygosity at the time of CD19– relapse to chimeric antigen receptor (CAR) therapy. The mutations are present in the vast majority of resistant tumor cells and are predicted to lead to a truncated protein with a nonfunctional or absent transmembrane domain and consequently to a loss of surface antigen. This irreversible loss of CD19 advocates for an alternative targeting or combination CAR approach. Mutations in theCD19 gene suggesting irreversible loss of its surface expression are identified in the majority of analyzed cases of CD19– relapse in two clinical trials of pediatric ALL CD19 CAR T therapy, offering considerations for the rational choice of follow-up therapies.